Workplace violence against healthcare professionals: A systematic review - Mento, Carmela; Silvestri, Maria Catena; Bruno, Antonio; Muscatello, Maria Rosaria Anna; Cedro, Clemente; Pandolfo, Gianluca; Zoccali, Rocco A. (Aggression and violent behavior, 2020)
Workplace violence is defined as an aggression when staff members are abused, intimidated or attacked in circumstances related to their work, including commuting to and from work, involving an explicit or implicit challenge to their safety, well-being or health. Violence against healthcare professionals is frequent, and constitutes a source of concern in the health system. Scientific literature highlights negative behavioral, emotional, cognitive and physical outcomes. The aim of this review is to examine the impact that exposure to workplace violence against healthcare professionals can produce, to improve healthcare professionals' knowledge about the consequences of workplace violence, and to guide future research in identifying strategies that could effectively reduce the incidence of workplace violence. We have conducted, in accordance with PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines, a systematic search for the literature on PubMed. Search terms related to WPV were (“Workplace violence”, “Aggression”, “Aggression department emergency”), and search terms related to WPV consequences were (“Mental health”, OR “Health care workers”, OR “Burnout”). Initial search identified 1.434 articles. One-hundred publications have been selected and the relevant publications, appropriate to the topic review, was reduced to twenty-seven. According to examined literature, workplace violence mostly occurs in psychiatric departments, emergency services, polyclinics/waiting rooms, and geriatric units. Negative factors such as lack of information, insufficient personnel and equipment, and communication breakdowns increase the risk of violent behavior in healthcare services. Most violence in health institutions is perpetrated by patients and their relatives in the forms of verbal abuse, psychological violence, physical assault, and sexual abuse. Workplace violence might lead to various negative impacts on health workers' psychological and physical health, such as increase in stress and anxiety levels; feelings of anger, guilty, insecurity, burnout. •Violence against healthcare professionals is frequent, and constitutes a source of concern in the health system.•Scientific literature highlights negative behavioral, emotional, cognitive and physical outcomes against healthcare professionals•The aim of this review is to examine the impact that exposure to workplace violence against healthcare professionals can produce, to improve healthcare professionals’ knowledge about the consequences•The results guide future research in identifying strategies that could effectively reduce the incidence of workplace violence.